(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVE: The purpose of this study was to compare the fracture resistance of implant-supported all-ceramic fixed partial dentures, which have three different pontic designs. MATERIAL AND METHODS: Two implants were placed in a metal model simulating mandibular left second premolar and mandibular left second molar. Thirty standardized 3-unit all-ceramic fixed partial dentures with biconvex, convex or concave pontic designs were fabricated using IPS e.max system (n=10). Afterwards, specimens were centrally loaded on the pontics until failure with a universal testing machine. Results were analyzed by Kruskal-Wallis and Mann-Whitney U tests at 5% significance level. RESULTS: The fracture resistance values of all-ceramic fixed partial dentures designed with biconvex, convex or concave pontics were 349.71, 438.20 and 300.78 N, respectively. There were no statistically significant differences between the fracture resistances of the groups (p>;0.05), except for convex and concave groups (p